Effects of physical refuges on fish–plankton interactions - Bertolo, A.; Lacroix, G.; Lescher‐Moutouš, F.; Sala, S. (Freshwater Biology, 1999)
1.Refuges that reduce fish‐induced mortality of zooplankton are considered to be key factors in controlling phytoplankton growth in lake ecosystems. In order to better understand the role of physical refuges for zooplankton on zooplanktivorous fish‐plankton relationships, an enclosure experiment was run in a mesotrophic lake. Even‐link systems (zooplankton and phytoplankton) and odd‐link systems (zooplanktivorous fish, zooplankton and phytoplankton) were established. We also established an odd‐link system with a physical refuge for zooplankton where fish predation was limited in the upper half of the enclosure. 2.Fish negatively affected density and mean body length of herbivorous zooplankton and total zooplankton, filtering rates with some intermediate effects in the presence of the refuge. A clear refuge effect was observed for the dominant herbivore, Ceriodaphnia . On the other hand, the refuge seemed to increase the vulnerability of those taxa that aggregated in upper layers of the water column. Grazing was thus reduced in both odd‐link systems. 3.The lack of significant correlation between nutrient availability and phytoplankton biomass in enclosures suggested a top‐down control of algal growth in our experimental systems. In both odd‐link systems (‘fish’ and ‘refuge’) phytoplankton biomass was significantly enhanced, and transparency was reduced in comparison with the even‐link system.